Gerenciamento do cuidado ao idoso frágil em domicílio: capacitando cuidadores e familiares - Ferreira, Gilanne da Silva (2022)
Introduction: The process of caring for the frail elderly patient transits between the support ofcaregivers and/or family members, in addition to the support of the multiprofessional homecare team, which aims at offering integral care, based on technical, interdisciplinaryandaffective knowledge, in the search for enhancing the quality of life of the elderlyperson.Objectives: To search for scientific evidence on the care of the frail elderly; to analyzethecomplaints of family members and/or caregivers regarding the care of frail elderlypeopleandto build a care training program for family members and/or caregivers of frail elderlypeople.Method: This was a quanti-qualitative study, divided into three stages: constructionofasystematic review, field research, and construction of a technological product. ResultsandDiscussion: The research was carried out with 30 caregivers and 30 professionals fromtheSAD-JP. The caregivers pointed out difficulties in the mobilization of the elderly restrictedtothe bed, handling and hygiene in general, reporting the need of receiving orientations,capacitation and training by the health professionals of SAD-JP. It was noticed the prevalenceof the female gender in the caregivers' profile, most of them inserted in the double workday, forhaving other jobs, which can facilitate the mental illness rate in this public. In the questionnaireapplied with professionals from the SAD-JP, the research involved the multiprofessional team.The professionals pointed out the difficulty of the caregiver to promote the integral caretotheelderly, due to work overload, because besides the care assistance there are householdchoresthat need to be performed, also highlighting the insufficiency of inputs offered by publichealthservices for the elderly, but also the effectiveness of the work of professionals andcaregivers,enhancing the rehabilitation of the frail elderly. Finally, the professionals pointed out that theprevalent pathologies in the frail elderly are in the cardiovascular (heart diseases),osteomuscular (fractures and trauma in general), and neurological (stroke and Alzheimer'sdisease) systems. Realizing the need to promote, through the continuing educationstrategy,knowledge about caring for the frail elderly, the technological product was consolidatedinvideo lessons, in a didactic and playful way, with the following themes Drug administration;Positioning and mobilizations in bed; Guidelines how to prevent skin lesions causedbytheelderly's stay in bed; Hygiene and body care; Oral feeding, special diets and use of probes; Careof the tracheostomy; Social relations of the frail elderly and Mental health of the frail elderlyand the caregiver: self-care. Final Considerations: It is hoped that this work will contributetothe quality of life of the frail elder as well as to the daily dealings with the caregiver and/orfamily members, providing them with health education tools, thus promoting integral andhumanized care.